2022
DOI: 10.1162/neco_a_01447
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Attention Enhances Crowded Stimulus Encoding Across Modeled Receptive Fields by Increasing Redundancy of Feature Representations

Abstract: Any visual system, biological or artificial, must make a trade-off between the number of units used to represent the visual environment and the spatial resolution of the sampling array. Humans and some other animals are able to allocate attention to spatial locations to reconfigure the sampling array of receptive fields (RFs), thereby enhancing the spatial resolution of representations without changing the overall number of sampling units. Here, we examine how representations of visual features in a fully conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Our modeling approach allowed us to examine the theoretic impact of each change that is associated with gain systematically and quantify the potential benefit to detection and discrimination task performance. At larger scales or in other tasks there are theoretical reasons to expect that task performance will improve due to these effects, (Kay et al, 2015;Vo et al, 2017;Theiss et al, 2022) Whether our conclusions can generalize to the behavior of attentional gain in biological neural circuits is limited both by how well the neural network observer model approximates the functioning of those neural circuits and by the model's ability to predict behavior. There are several reasons to suggest that the model captures relevant properties of both object recognition and the primate visual system.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our modeling approach allowed us to examine the theoretic impact of each change that is associated with gain systematically and quantify the potential benefit to detection and discrimination task performance. At larger scales or in other tasks there are theoretical reasons to expect that task performance will improve due to these effects, (Kay et al, 2015;Vo et al, 2017;Theiss et al, 2022) Whether our conclusions can generalize to the behavior of attentional gain in biological neural circuits is limited both by how well the neural network observer model approximates the functioning of those neural circuits and by the model's ability to predict behavior. There are several reasons to suggest that the model captures relevant properties of both object recognition and the primate visual system.…”
Section: Discussionmentioning
confidence: 95%
“…Our modeling approach allowed us to examine the theoretic impact of each change that is associated with gain systematically and quantify the potential benefit to detection and discrimination task performance. At larger scales or in other tasks there are theoretical reasons to expect that task performance will improve due to these effects, ( Kay et al, 2015 ; Vo et al, 2017 ; Theiss et al, 2022 )…”
Section: Discussionmentioning
confidence: 99%
“…Our modeling approach allowed us to examine the theoretical impact of each change associated with gain systematically and quantify that these provided no benefit to detection or discrimination task performance. Nevertheless, previous modeling work has demonstrated that shift and shrinkage, in particular, can increase the resolution and redundancy of receptive field coverage ( Kay et al, 2015 ; Vo et al, 2017 ; Theiss et al, 2022 ). Our results differ along two important dimensions: first, we scaled the magnitude of shift, shrinkage, and sensitivity changes to those induced by Gaussian gain (at a gain strength that was matched to human performance) and these were in general equal to or smaller in magnitude to what was observed in these previous papers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RFs in humans and other animals have been observed to both shrink in size and shift toward the locus of attention with sustained spatial attention ( Womelsdorf, Anton-Erxleben, Pieper, & Treue, 2006 ; Klein, Harvey, & Dumoulin, 2014 ). Using computational modeling approaches, Baruch and Yeshurun (2014) showed that this reconfiguration of RFs with attention could explain a number of attentional effects on neural responses, and Theiss, Bowen, and Silver (2021) showed that a similar mechanism could be implemented in a convolutional neural network, resulting in attentional enhancement of performance on a visual crowding task. Additionally, He, Wang, and Fang (2019) showed that, after perceptual learning of a crowded orientation discrimination task, decreases in RF size of individual fMRI voxels in cortical area V2 correlated with improved performance that resulted from perceptual learning.…”
Section: Discussionmentioning
confidence: 99%
“…Crowding has been modeled as arising from inherent limits in the size and density of cortical receptive fields (RFs) in the visual periphery, especially when compared with central vision ( Parkes, Lund, Angelucci, Solomon, & Morgan, 2001 ; Balas, Nakano, & Rosenholtz, 2009 ; Dakin, Cass, Greenwood, & Bex, 2010 ; Greenwood, Bex, & Dakin, 2010 ; Freeman & Simoncelli, 2011 ; Rosenholtz, 2016 ). One mechanism by which visual spatial attention might relieve crowding is by locally increasing the density of RFs that sample the target location ( Baruch & Yeshurun, 2014 ; Theiss, Bowen, & Silver, 2021 ). Neurophysiologically, it has been shown that sustained visual spatial attention causes RFs to shift toward the locus of attention and to shrink in size ( Womelsdorf, Anton-Erxleben, Pieper, & Treue, 2006 ; Klein, Harvey, & Dumoulin, 2014 ).…”
Section: Introductionmentioning
confidence: 99%